Four Crystalline Forms of (Tetrahydrothiophene)trichloridogold(III): Polymorphism and Reversible Low‐temperature Phase Transitions. Issue 4 (17th January 2017) - Upmann, Daniel; Näther, Christian; Jess, Inke; Jones, Peter G.
Abstract : The title compound (tht)AuCl3, previously known to crystallize at –95 °C in space group C 2 with Z = 4 (formI ), converts reversibly to formII ( P 21 / n, Z = 8) at ca. –150 °C; the b axis doubles and the centering is lost. A few crystals of a rarer formIII ( Pna 21, Z = 4) were also investigated; these transform reversibly to formIV ( P 21 / c, Z = 4) at ca. –160 °C. In all forms, stacks of molecules are formed, with short Au··· Cl contacts within the stacks. For formsI andII, adjacent stacks are connected by C–H··· Cl interactions; more striking for formsIII /IV are short Cl··· Cl contacts between the stacks. Detailed physico‐chemical studies of the relationships between the various phases proved to be impossible, largely because formIII could not be obtained reproducibly in significant quantities. Abstract :